An Efficient Synthesis of 3-Aryl-2H-chromene Derivatives as Potential Bone Anabolic Agents - Khanka, Sonu; Rawat, Kundan S.; Pandey, Priyanka; Pal, Shyamal; Vats, Ravi P.; Rathur, Rajat; Sharma, Kriti; Dipali, Divya; Singh, Divya; Goel, Atul (Synlett, 2025)
In a quest to identify new osteogenic agents, a new series of 3-aryl-2H-chromene derivatives were rationally designed based on natural isoflavonoids and synthesized through ring transformation of 2H-pyran-2-ones with 3-acetyl-2H-chromene derivatives. From primary screening, five compounds were found to be active in osteoblast differentiation. Among these, the most active compound, 3-(7-methoxy-2H-chromen-3-yl)-5-piperidin-1-ylbiphenyl-4-carbonitrile, showed significantly enhanced calcium nodule formation at 1 pM and 100 pM, and increased osteoblast cell viability. Western blotting experiments indicate that this chromene upregulated osteogenic marker genes such as RUNX2, BMP2, and Type 1 col at the transcriptional and translational levels at concentrations of 1 pM and 100 pM. Furthermore, it decreased osteoblast cell apoptosis at 1 pM and 100 pM, while increasing cell survival in serum-deprived conditions. All these results suggested that the compound has great potential as a bone anabolic agent to improve bone health.
Keywords: chromenes; bone anabolic agents; medicinal chemistry; osteoblast differentiation; ring transformation reaction; pyranones